2019
DOI: 10.3382/ps/pey399
|View full text |Cite
|
Sign up to set email alerts
|

How can heat stress affect chicken meat quality? – a review

Abstract: Heat stress is one of the most important environmental stressors for the poultry industry in the world. Reduced growth rate, low feed efficiency, impaired immunological responses, changes in intestinal microflora, and deterioration of meat quality are the consequences of acute or chronic heat stress. In terms of meat quality, 3 primary mechanisms have been suggested to explain this phenomenon: 1) rapid drop in pH during and after slaughter due to the glycogen conversion to increase in lactic acid accumulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
123
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(149 citation statements)
references
References 76 publications
2
123
1
3
Order By: Relevance
“…Former studies reported that heat stress had detrimental effects on meat quality and even resulted in pale, soft, and exudative-like meat, decreasing consumers' acceptability and economic loss ( Zaboli et al., 2019 ). In this study, heat stress induced poor meat quality by lowering pH 24h and increasing cooking loss.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Former studies reported that heat stress had detrimental effects on meat quality and even resulted in pale, soft, and exudative-like meat, decreasing consumers' acceptability and economic loss ( Zaboli et al., 2019 ). In this study, heat stress induced poor meat quality by lowering pH 24h and increasing cooking loss.…”
Section: Discussionmentioning
confidence: 99%
“…Heat stress is one of the major environment stressors in poultry production because it adversely affects health status and production performance of broilers, causing direct economic losses ( St-Pierre et al., 2003 ). Broilers exposed to heat stress would induce multiple physiology disturbances, such as endocrine disorders ( Rajaei-Sharifabadi et al., 2017 ), immune suppression ( Wang et al., 2018 ), and oxidative stress ( Ganesan et al., 2017 ; Zhang et al., 2018 ) and adversely affect the meat quality by changing muscle glycolysis metabolism and oxidative status ( Zaboli et al., 2019 ). Either acute or chronic heat stress had detrimental effects on meat quality by increasing postmortem glycolytic metabolisms ( Zhang et al., 2012 ; Zaboli et al., 2019 ) and induced a lower ultimate pH accompanied with variation in water-holding capacity, meat color, and tenderness of meat, resulting in a lower purchasing desire ( Zhang et al., 2012 ; Wang et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these artificial selection pressures have been largely consumer-driven, focusing solely on improving certain commercially attractive parameters at the expense of immune, metabolic, and skeletal function [4]. As a result, the modern broiler has become increasingly susceptible to the effects of thermal and, in turn, oxidative stresses [5].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the poultry industry has exerted many artificial selection pressures on broiler chickens in order to breed for commercially desirable traits, mainly faster growth rates, increased breast meat yield, and improved feed-conversion ratios [4,5]. However, the industry's narrow focus on body weight has inadvertently resulted in several adverse effects, including immune and metabolic dysfunction as well as increased metabolic costs [6]. Broiler chickens are classified as homoeothermic animals, meaning that they can only maintain their body temperature efficiently when ambient temperatures are within certain limits [7,8].…”
Section: Introductionmentioning
confidence: 99%